Типологія характерів прози 1960-х років - Михайличенко, Г.Б. (Культура народов Причерноморья, 2013)
У статті розглядаються новий аспект характеротворення у новому циклі 60-х років в
українській літературі. Визначено типологію цього процесу на прикладі прози В. Дрозда, основними з
яких виявлено мотив «воєнного дитинства». Це пов’язано з тим, що з кінця 1950-х років змінюються
структурні домінанти образотворення, джерелом яких стає не життя народу, а життя особистості,
її духовний світ, заснований на ієрархічних законах. В основу цієї ієрархії кладеться “особиста
пережитість” зображеного. Відтак, точкою відліку стає дитинство ліричного героя, становлення його
характеру, виникнення основних його життєвих орієнтирів. Отже, історія народу поступилася своїм
місцем історії особистості, а базовий до цього “принцип історизму” одержав у літературі цілком
несподіване втілення, наблизивши її до справжнього психологізму. В статье рассматривается новый аспект создания характеров в новом цикле 60-х годов в
украинской литературе. Определена типология этого процесса на примере прозы В. Дрозда, основным
из которых выявлен мотив «военного детства». Это было связано с тем, что с конца 1950-х годов
изменяются структурные доминаты создания образов, источником чего становится не жизнь народа,
а жизнь индивидуальности, ее духовный мир, основанный на иерархических законах. В основу такой
иерархии кладется “личностная пережитость” изображения. Таким образом, точкой отсчета
становится детство лирического героя, становление его характера, формирование его жизненных
ориентиров. В итоге история народа уступает место личности, а базовый до этого ”принцип
историзма” получает в литературе совершенно неожиданное воплощение, приблизивши ее к
настоящему психологизму. In the article is being considered a new aspect of creating characters in a new cycle of the Ukrainian
literature in the 60-ies. The typology of this process has been determined after the example of B. Drozdʼs prosa,
which main motive is considered to be «war-time childhood».
It is pointed out that the 60-ies of the 20-th century became the principle turning point of the creation of
characters. It presents quite a new cycle, in which the direction of the article typification has been changed
diametrically: an ideological standard regarding a real person has change into a standard of human qualities
which became the source of the artistic ideas. The vector of the literature priorities abruptly turned away from
ideological schemes of the real life and real fact have been preferred to the fact.
It is possible to retrace the evolution of this process by the way of prosa lirization: stories, narratives are filled
up with personal experiences. To designate this phenomenon a term «autophsychological documentary» has
been used. It implies the auter portraying, depicting war-time happenings which changed to inner private
perception of the world.
The history of the people in the prosa of the 60-ies leaves place to the history of a personality. This,
paradoxically fundamental base of Marxism was incorporated into the real phsycologism.
As a «beginning» of the human history became the childhood which explains the special writer’s attention after
creation cinema narration «Charmed Desna» devoted this period of human life.
As a result a conclusion was made than the motive of the childhood has become typical at this considered
moment, more over – conceptual.